Exploring aspects of art, culture and Society in today's world - Syafira, Yumni (Journal of Studies on Art, Culture and Society, 2024)
Today's world is complex, dynamic and diverse. It has different aspects of art, culture and Society that interact and influence each other. This study aims to explore these aspects through a multidisciplinary and critical approach. This study uses qualitative methods and case studies as the research strategy. Data were collected through observations, interviews and document analysis. The results of this study show that the fields of art, culture and Society in the contemporary world have unique characteristics such as creativity, innovation, plurality, hybridity, globalization and resistance. The research also reveals some of the challenges and opportunities facing actors in art, culture and Society in today's world, such as issues of identity, freedom of expression, human rights, social justice and sustainable development. This research will likely contribute to developing the science and practice of art, culture and Society in today's world.